How can new farmers improve their entrepreneurial performance? Qualitative comparative analysis based on fuzzy sets - Luo, Shudan; Zhou, Pengfei; Shen, Yang (Frontiers in Sustainable Food Systems, 2024)
Based on the configuration theory, this paper discusses the multiple concurrent causes and causal complex mechanisms affecting the performance differences among different new farmers. Using the fuzzy set qualitative comparative analysis method, taking 40 cases of CCTV's "ZHI FU JING" column as samples, the paper analyzes the necessary conditions for new farmers to produce high performance by the anthefactory-variable configuration composed of human capital, social capital, psychological capital, entrepreneurial learning and entrepreneurial opportunity identification. The results show that: (1) High human capital is the necessary core condition for new farmers to produce high entrepreneurial performance, lack of high entrepreneurial learning and lack of high entrepreneurial opportunity identification is the core necessary condition for low entrepreneurial performance; (2) The driving mechanism of new farmers' high entrepreneurial performance is divided into three paths, and the driving mechanism of new farmers' low entrepreneurial performance is divided into two paths; (3) The ways of inhibiting new farmers' performance and promoting their performance are asymmetrical.Keywords：New farmers; Entrepreneurial performance; Human capital; Driving mechanism; fsQCARural development is a pivotal component in the attainment of the Sustainable Development Goals (SDGs) for 2030, with Sustainable Development Goal 2 (SDG 2) explicitly emphasizing the significance of bolstering and reinforcing family farming. Family farming plays a key role within the globe, contributing to rural employment and economic growth (Saridakis et al., 2021). In light of globalization, rural development is not only an international issue, but also a focus of attention for China as an agricultural powerhouse. In the new stage of development, the issue of "agriculture, rural areas and farmers" is the top priority of the whole Party's work, and the rural revitalization is the general grasp of "agriculture, rural areas and farmers" work. The No.1 Central Document of 2023 proposed to accelerate the high-quality development of rural industries, support and encourage rural